Analysis of new multi-priority P-CSMA of non-persistent type random multiple access ad hoc network in MAC protocol analysis. (4th May 2020) - Zejun, Han; Hongwei, Ding; Liyong, Bao; Zhijun, Yang; Qianlin, Liu
A multichannel non-persistent of P-CSMA (NP-CSMA) random multiple access ad hoc network in MAC protocol based on variable collision length is proposed. It has important applications value in wireless ad hoc network and so on. When the channel is idle, the end-users are sent by P probability; while the channel is busy, it will not listen to the channel and wait for a certain period of time to send it again. The multi-priority mechanism is introduced to meet the needs of QoS in different priorities. By modelling the new multi-priority NP-CSMA protocol, the throughput of each channel is obtained by using the average cycle method. Compared with other protocols, the superiority of this protocol is obtained, and the accuracy of the protocol is verified through simulation experiments.